ASPEK-ASPEK REVITALISASI KAWASAN SITUS KALI RAJA KABUPATEN RAJA AMPAT - Sri Chiirullia Sukandar (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2012)
Kali Raja site has the potential to be developed as a tourist destination. Thus it is necessary to revitalize the cultural heritage sites in the Kali Raja. As for the goal of this research is the potential for archaeological sites in Kampung Wawiyai, District of South Waigeo like of them in the cliff wall paintings, and Telur Raja as part of the origin of Raja Ampat, which is located on the banks of Kali Raja. Research targets primarily spatial sites, cultural potential around the site, the potential of natural resources, public opinion and the role of government as policy makers. Kali Raja revitalization site is intended to regrow important values such as cultural sites. Kali Raja order site is also useful for the general public and in particular to the Raja Ampat current generation and the generations to come the following aspects have been identified, namely the aspect of value, ideological aspects, aspects of knowledge is science, socio-cultural, economic aspects, public participation aspects, and aspects of development.